Aplikasi Website Pengajuan Cuti Karyawan Rumah Sakit Islam Assyifa Sukabumi Berbasis Whatsapp Blast - Firmansah, D A; Rohman, R S; Farlina, Y (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
Assyifa Islamic Hospital is an Islamic hospital in Sukabumi that is very concerned about the welfare of its employees. One of the clear evidence of the implementation of this intention is in the form of granting annual leave allowances for each employee. To support the process of filing this leave required a good system by utilizing the existing website and smartphone devices owned by each employee. This of course can be done easily and more quickly because every employee who will apply for leave is only enough to access the website pages that have been determined. The process of submitting leave will be automatically known by the related supervisors, considering that the employee leave submission notification can be sent directly to the supervisor's related number whatsapp so that the verification process of submission can be done in real time by the related supervisor. With this system, the data recapitulation process will take place faster because employee leave is very influential on the employee service schedule of each division in the Sukabumi Assyifa Department, which in turn will have an impact on giving incentives to each employee.